The general solutions of difference vector-equations with constant coefficients - Štikonas, Artūras (Lietuvos matematikos rinkinys, 2000)
This paper deals with general solutions of difference vector-equations with constant coefficients. We find the simple formulae between solution of the first order homogeneous differential equations and solution of difference equation. This allows easily get all solutions of difference equations if we know the differential solution.